Evaluation of a strategic academic-government partnership to advance COVID-19 clinical practice guidelines access and uptake in South Africa - Taryn Young; Tamara Kredo; Bey-Marrié Schmidt; Nasreen Jessani; Trudy Desirie D Leong (BMJ Global Health)
Introduction Academic–government partnerships are important to advance timely, responsive and relevant evidence for decision-making (policy, guideline, law and regulation) deliberations. Deliberate and strategic integrated knowledge translation (KT) approaches within such partnerships have been shown to facilitate evidence-informed decision-making (EIDM). We used Cochrane’s KT Framework to map and analyse COVID-19 response activities instituted by a strategic academic-government partnership to support EIDM during the COVID-19 pandemic in South Africa.Methods We used Cochrane’s KT Framework to map and analyse COVID-19 response activities instituted by a strategic academic–government partnership to support EIDM during the COVID-19 pandemic in South Africa. The COVID-19 response activities included coproducing rapid therapeutics reviews, engaging stakeholders with review evidence, packaging and disseminating review products, facilitating access to rapid reviews for evidence users and adapting partnership processes for rapid review production.Results This paper highlights the importance of (a) authentic partnerships between evidence producers and users (motivated by context-specific goals, trust and relationships); (b) intentional and systematic stakeholder engagement to promote the rapid exchange of information; (c) using tailored, responsive and relevant KT to promote the uptake of evidence and (d) monitoring and evaluating the implementation of KT to identify lessons learnt and adaptation of KT approaches.Conclusion In responding to future emergencies, a comprehensive KT strategy, including the expertise of KT practitioners and science communicators to make evidence and guideline recommendations accessible, should be embedded. Additionally, streamlining bureaucratic processes for approving and communicating information; identifying and addressing decision-maker capacity needs; engaging a range of stakeholders and integrating KT in usual decision-making processes, is recommended. Adequate investment by governments is needed for sustaining KT approaches that can enhance EIDM for improving public health outcomes.